Chelonitoxism outbreak caused from consuming turtle, Eastern Samar, Philippines, August 2013 - Ventura, Ray Justin Cacho; Ching, Paula Katrina; de los Reyes, Vikki Carr; Sucaldito, Ma Nemia; Tayag, Enrique (Western Pacific Surveillance and Response, 2015)
Background On 21 August 2013, the Event-based Surveillance and Response (ESR) of the Department of Health, Philippines captured a foodborne illness event among residents of a coastal village in Eastern Samar Province, Philippines. The suspected cause was the consumption of a sea turtle found near the village. A team from the Department of Health was sent to conduct an outbreak investigation. Methods A cohort study was done. A case was defined as any person in Arteche, Eastern Samar who developed dry mouth and burning sensation in the throat from 15 August to 27 August, 2013. Severity of the disease was classified as mild, moderate, and severe. We conducted records review, environmental investigation, and interviewed key informants. Results Sixty-eight cases were identified; four died (CFR = 6%). All cases had history of turtle meat consumption. Dose dependent relationship was noted between amount of turtle meat consumed and risk of illness. In the cohort study male sex and consumption of turtle-meat were associated with illness. Conclusion In conclusion, this study was able to identify the turtle meat as the source of this foodborne outbreak. This study emphasizes the dangers of consuming turtle meat. The reported cases of turtle meat poisoning in the Philippines proves that consumption of this animal is an ongoing practice in the country. By publishing information about sea turtle poisoning outbreaks in the Philippines we hope to raise awareness of the potential severe health effects from ingesting these endangered animals.